Division of Inheritance of Mafqud Husband According to the Opinion of the Ulama of Langsa City - Muhammad Ikbal; Sahmiar Pulungan; Akmaluddin Syaputra (Dinasti Research, 2024)
The purpose of this research is to find out how the review of the mafq?d husband according to Islamic law and to find out the views of the Ulama of Langsa City regarding the distribution of the inheritance of the mafq?d husband. Based on the results of the research, it is concluded that in Islamic law, a mafqud (missing) husband is considered to have died after a waiting period, generally four years, in accordance with the Shafi'i Mazhab. If the mafqud husband has not been found within this period, then his status is considered legally dead, even though there is no physical evidence of his death. During this waiting period, the mafqud husband's property is still managed with the principle of prudence, and the arrangement and use of the property is done in a way that preserves the rights of the heirs and prevents potential conflicts. Langsa City scholars, such as Abati Salahuddin, Tgk. Syibral Malasyi, Tgk. Hadi Subulana, Abi Rifana, and Walidi Ramli Amri, identified two main situations related to mafqud husbands in the context of inheritance distribution. First, if the mafqud husband is found alive after the waiting period, the property that has been distributed remains the property of each heir in accordance with the provisions that apply at that time. Second, if the mafqud husband is not found within four years and is considered dead, then his inheritance can be distributed to the heirs in accordance with the provisions of Islamic law after the court process establishes the status of his death. They emphasized the need for careful and fair management of the estate during the waiting period as well as the judge's decision to ensure the distribution of the estate in accordance with sharia.